THE INFLUENCE OF UNFAVORABLE ENVIRONMENTAL FACTORS ON THE STATE OF CHILDREN'S DENTAL HEALTH (LITERATURE REVIEW) - M.A. Luchynskyi (Ukrainian Medical Stomatological Academy, 2015)
In the article the literature on the influence of anthropogenic factors on the development of children's basic dental diseases has been reviewed. It is shown that unfavorable environmental factors contribute to the development of oral diseases. Also, in children living in unfavorable environmental conditions the diseases occur in more severe forms.